Опасность предельного уровня: [роман] / Сергей Самаров - Самаров Сергей Васильевич (Спецназ ГРУ, 2007)
Экземпляры: РБАБ () / Инвентарный номер: 39670 / Цена: 85.00 / Авт.знак: С 17 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6